Psychology, religion, and the nature of the soul a historical entanglement - Richards, Graham 1941-; SpringerLink (Online service). (New York Springer, 2011)
Neither a book about the psychology of spirituality nor America?s ongoing turf wars between religion and science, Psychology, Religion, and the Nature of the Soul takes to task many of the presumed relationships between the two?from sharing common concerns to diametrically hostile opposites?to analyze the myriad functions religion and psychology play in our understanding of the human life and mind. Graham Richards takes the historical and philosophical long view in these rigorous and readable essays, which trace three long-running and potentially outmoded threads: that psychology and religion are irrelevant to each other, that they are complementary and should collaborate, and that one will eventually replace the other. He references a stunning variety of texts (from Freud and Allport to Karen Armstrong and Paul Tillich) reflecting the evolution of these ideas over the decades, to emphasize both the complexity of the issues and the enduring lack of easy answers. The eloquence of the writing and passionate objectivity of the argument will interest readers on all sides of the debate as the author examines: ? The religious origins of psychology. ? The original dichotomy: mythos versus logos. ? The authenticity of religious experience. ? Religion and personality. ? The problematic role of prayer. ? Religion in the history of psychotherapy. For those making a serious study of the history of psychology, Psychology, Religion, and the Nature of the Soul will inspire a fresh wave of critical discussion and inquiry.
The nature of the problem -- Mythos and logos -- Psychology's religious roots. Education and the child ; The American dimension ; Some early British religious psychologists ; A Catholic detour ; Religious origins of the concept of "psychology" ; Conclusions -- Psychology of religion. William James? the varieties of religious experience ; Classic psychology of religion ; The demise of classical psychology of religion ; Conclusion -- A boundary problem. John Macmurray ; Reinhold Niebuhr ; Paul Tillich ; Martin Buber ; The Union Theological Seminary connection ; Conclusion -- The authenticity of religious experience -- Religion and psychotherapy. Boston Emmanuel Movement (1906-1929) ; Britain between 1918 and c. 1980 ; The growth movement -- The problem of prayer -- Religion and personality -- The theism question -- Psychology and non-Christian religions -- Religion and psychological theory. Piaget : salvaging Protestantism by other means? ; Freud : the mysterious nature of psychoanalysis ; Gordon W. Allport (1897-1967) : the psychology of an Episcopalian ; Atheism and anti-religious psychology ; Conclusion -- Conclusions, hypotheses, suggestions and a stab at a personal "position statement". Religious doctrines beyond psychology?s brief ; Religion and psychology essentially concerned with the same issues ; Religion is an inferior alternative to psychology ; Reconstructing the relationship ; Two issues for historians of psychology ; An attempt at a final position ; Concluding remarks.
Electronic reproduction.
Keywords: Psychology and religion; Psychology, Religious; Religion and psychology; Psychology and religion; Electronic books